Validity of detrended fluctuation analysis of heart rate variability to determine intensity thresholds in elite cyclists - Mateo-March, Manuel; Moya-Ramón, Manuel; Javaloyes, Alejandro; Sánchez-Muñoz, Cristóbal; Clemente-Suárez, Vicente J. (European journal of sport science, 2023)
Background: The evaluation of performance in endurance athletes and the subsequent individualisation of training is based on the determination of individual physiological thresholds during incremental tests. Gas exchange or blood lactate analysis are usually implemented for this purpose, but these methodologies are expensive and invasive. The short-term scaling exponent alpha 1 of detrended Fluctuation Analysis (DFA-α1) of the Heart Rate Variability (HRV) has been proposed as a non-invasive methodology to detect intensity thresholds. Purpose: The aim of this study is to analyse the validity of DFA-α1 HRV analysis to determine the individual training thresholds in elite cyclists and to compare them against the lactate thresholds. Methodology: 38 male elite cyclists performed a graded exercise test to determine their individual thresholds. HRV and blood lactate were monitored during the test. The first (LT1 and DFA-α1-0.75, for lactate and HRV, respectively) and second (LT2 and DFA-α1-0.5, for lactate and HRV, respectively) training intensity thresholds were calculated. Then, these points were matched to their respective power output (PO) and heart rate (HR). Results: There were no significant differences (p > 0.05) between the DFA-α1-0.75 and LT1 with significant positive correlations in PO (r = 0.85) and HR (r = 0.66). The DFA-α1-0.5 was different against LT2 in PO (p = 0.04) and HR (p = 0.02), but it showed significant positive correlation in PO (r = 0.93) and HR (r = 0.71). Conclusions: The DFA1-a-0.75 can be used to estimate LT1 non-invasively in elite cyclists. Further research should explore the validity of DFA-α1-0.5. Highlights The power and heart rate values derived from the DFA-α1-0.75 threshold showed high levels of validity and agreement when they were compared against the first lactate threshold. The second lactate threshold and the DFA-α1-0.5 were different (p < 0.05) but showed high levels of correlation. The detrended fluctuation analysis is a valid method to estimate the first lactate threshold and more studies are needed to verify its validity with the second lactate threshold.